Cascading effects of elevated ozone on wheat rhizosphere microbial communities depend on temperature and cultivar sensitivity. (November 2018) - Changey, F.; Bagard, M.; Souleymane, M.; Lerch, T.Z.
Abstract: Tropospheric ozone (O3 ) concentrations have now reached levels that can potentially affect crop production in several regions of the world. The interacting effects of the elevated O3 and temperature on plants are still unclear and their consequences on the rhizosphere microbial communities never studied yet. Here, we conducted a 3-week fumigation experiment on two cultivars of wheat with different tolerance to O3 (Premio and Soissons) at two temperatures (20 °C and 30 °C). The impacts of O3 were measured on plants physiology, rhizosphere chemical environment and microbial communities. Globally, most of the results showed that elevated O3 effects were more pronounced at 20 °C than 30 °C, especially on the most O3- sensitive cultivar (Soissons). Elevated O3 reduced significantly plant root biomass (up to −37% for Soissons) compared to non-fumigated plants. A decrease in the dissolved organic matter with a relative increase of aromatic compounds concentration was also observed under elevated O3, suggesting quantitative and qualitative impacts on roots exudation. While bacterial abundance was negatively affected by O3 plant stress, fungal abundance was found to be stimulated (up to 12 fold compared to non-fumigated plants for Soissons at 20 °C). These changes were accompanied by modifications of the genetic structures and metabolic profiles, with a relative increase of amino acids catabolism. This fully controlled laboratory experiment showed that the effects of elevated O3 on soil microbial communities i) are plant-mediated and depend on the cultivar sensitivity, ii) decrease in warming condition, iii) increase the fungi to bacteria ratio and iv) alter both the genetic structure and the metabolic activities. This study highlights the importance of considering interactive effects between pollutants and climate changes on plant-microbe relationship to better inform models and improve predictions of future states of agroecosystems. Graphical abstract: Image 1 Highlights: Elevated O3 effects on plants were more pronounced at 20 °C than 30 °C. Elevated O3 increases rhizosphere fungal abundance but decrease bacterial one. Elevated O3 changes microbial structures and catabolic profiles. Abstract : The effects of elevated ozone on wheat rhizosphere microbial communities are more pronounced at 20 °C than 30 °C and on the most sensitive cultivar.